Progress in the Caribbean region on commitments to children's rights - Bernard, Desiree (CCS [Georgetown]GY, 2008)
Focuses on issues that affect children which are of concern to the Caribbean region viz. abuse and violence; drug use and trafficking; prostitution and pornography; teen-aged pregnancies; and, abdication of parental responsibilities.